1997
DOI: 10.1007/3-540-62495-3_33
|View full text |Cite
|
Sign up to set email alerts
|

Bipartite embeddings of trees in the plane

Abstract: Given a tree T on n vertices and a set P of n points in the plane in general position, it is known that T can be straight line embedded in P without crossings. Now imagine the set P is partitioned into two disjoint subsets R and B, and we ask for an embedding of T in P without crossings and with the property that all edges join a point in R (red) and a point in B (blue). In this case we say that T admits a bipartite embedding with respect to the bipartition (R, B). Examples show that the problem in its full ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 6 publications
(4 reference statements)
2
52
0
2
Order By: Relevance
“…It is shown that if R and B are separated by a line and |R| = |B|, then there exists a non-crossing geometric alternating path that passes through all the points in R ∪ B [1]. On the other hand, as we show in Figure 4 (c), there exists a configuration consisting of six red points and seven blue points in the plane for which there exists no non-crossing geometric alternating path P 13 that passes through all these 13 points.…”
Section: Theorem 23 (The Equitable Subdivision Theoremmentioning
confidence: 99%
“…It is shown that if R and B are separated by a line and |R| = |B|, then there exists a non-crossing geometric alternating path that passes through all the points in R ∪ B [1]. On the other hand, as we show in Figure 4 (c), there exists a configuration consisting of six red points and seven blue points in the plane for which there exists no non-crossing geometric alternating path P 13 that passes through all these 13 points.…”
Section: Theorem 23 (The Equitable Subdivision Theoremmentioning
confidence: 99%
“…Abellanas et al [2] proved that there exists a plane bichromatic tree on R ∪ B whose maximum vertex degree is O(k + log |B|). Kaneko [9] showed how to compute a plane bichromatic tree of maximum degree 3k.…”
Section: Previous Workmentioning
confidence: 99%
“…Abellanas et al [2] considered the problem of computing a low degree plane bichromatic tree on some restricted point sets. They proved that if R ∪ B is in convex position and |R| = k|B|, with k 1, then R ∪ B admits a plane bichromatic tree of maximum degree k + 2.…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations